Public health event communications under International Health Regulations (2005) in the Western Pacific Region, September 2006-January 2017 - Li Xi; Li Ailan (World Health Organization Regional Office for the Western Pacific, 2019)
The International Health Regulations, or IHR (2005), establishes timely communication between the World Health Organization (WHO) and Member States to manage acute public health events and protect health security. Experiences of the WHO IHR contact point for the Western Pacific Region demonstrated the communication mechanism has achieved its functions in the Region. Investment in IHR communication as part of the Asia Pacific Strategy for Emerging Diseases and Public Health Emergencies (APSED III) during peaceful times between public health emergencies builds capacity, confidence and trust in information sharing during emergencies. IHR communication is integral to the national, regional and global epidemic intelligence and risk assessments system. Regular simulation exercises (for example, IHR Exercise Crystal) play an important role in testing and strengthening IHR communication. IHR communication continues to be vital for Member States and WHO Country Offices to advise on health security.